Online Sexual Solicitation - Kate Fogarty (EDIS)
“Internet connectivity in the form of blogs, chat rooms, and forums can be hazardous to our teens today. These online communication aids are not themselves the problem; rather, teens face an ever-present threat of being sexually solicited online.” This 2-page Family Album Radio transcript was written by Kate Fogarty and published by the UF Department of Family, Youth and Community Sciences, March 2012.